Integrated fuel cell bipolar plate and preparation method thereof
By using polyvinyl alcohol, expanded graphite, borax and conductive polyaniline, the integrated fuel cell bipolar plate is directly prepared, which solves the problems of complex preparation, high cost and low sealing qualification rate of existing bipolar plates, and achieves efficient and economical production and good performance.
Patent Information
- Application Number
- CN202411785380.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-12-06
AI Technical Summary
The preparation process of existing fuel cell bipolar plates is complex, has high cost and low sealing pass rate, which is not conducive to the disassembly, assembly and re-repair of the stack.
Polyvinyl alcohol is used as the pore-making material, expanded graphite is used as the graphite material, borax is used as the crosslinking agent, and conductive polyaniline is used as the adhesive. The integrated fuel cell bipolar plate is prepared by direct preparation, reducing the integration process and improving production efficiency and performance.
It simplifies production processes, reduces costs, improves sealing qualification rate and performance, and is suitable for large-scale production to meet the use needs of fuel cells.
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of fuel cells, and in particular relates to an integrated fuel cell bipolar plate and a preparation method thereof. Background Art
[0002] The bipolar plate (BP) of a fuel cell, also known as the flow field plate, is the "skeleton" of the fuel cell stack. It is assembled with the membrane electrode layer to form a fuel cell stack. It plays the role of supporting, collecting current, providing channels for coolant, and separating oxidants and reductants in the fuel cell.
[0003] At present, common bipolar plates (such as graphite engraving plates, metal bipolar plates and flexible graphite bipolar plates) are basically made of two single plates by gluing or welding, and then stacked with membrane electrodes; some of them integrate membrane electrodes and plates into a single cell, and stack them with single cells as units; others do not integrate plates with plates or plates with membrane electrodes, and directly stack cathode plates / anode plates / membrane electrodes. By integrating bipolar plates by gluing plates with plates or plates with membrane electrodes, the process is complicated, and there is a risk of damage or unqualified sealing, which increases manufacturing costs. If the common method is not used for integration, three strips of adhesive are required in a set of plates / membrane electrodes, which increases the unqualified sealing rate, and is not conducive to the disassembly and repair of the battery stack, and it is difficult to meet the needs of actual production and use. Summary of the invention
[0004] The embodiment of the present invention provides an integrated fuel cell bipolar plate and a preparation method thereof, aiming to solve the technical problems of the existing bipolar plates, such as complex preparation process, high preparation cost, low sealing qualification rate, and inconvenience in disassembly and repair of the fuel cell stack.
[0005] In order to solve the above technical problems, on the one hand, an embodiment of the present invention provides a method for preparing an integrated fuel cell bipolar plate, comprising the following steps:
[0006] S01, evenly laying a first mixed powder in a mold to obtain a first mixed powder layer; evenly laying a formed pore-forming material on the first mixed powder layer to obtain a formed pore-forming material layer; evenly laying a second mixed powder on the formed pore-forming material layer to obtain an integrated plate powder;
[0007] S02, press-forming the integrated plate powder at 140° C. to 160° C. to obtain an integrated plate; heating the integrated plate to 200° C. to 230° C. and maintaining for 2 h to 3 h to obtain an integrated bipolar plate having a cathode flow channel, an anode flow channel and a water flow channel;
[0008] S03, immersing the integrated bipolar plate having the cathode flow channel, the anode flow channel and the water flow channel in acrylic glue, rinsing after vacuum pressure immersion, and then curing to obtain an integrated fuel cell bipolar plate.
[0009] As a preferred embodiment, in step S01,
[0010] The first mixed powder and the second mixed powder are both graphite / adhesive mixed powders; the mass ratio of the first mixed powder to the second mixed powder is 1:1.
[0011] The graphite / adhesive mixed powder is prepared by the following method: 75% to 85% of graphite and 15% to 25% of adhesive are uniformly mixed by dry powder spraying to obtain the graphite / adhesive mixed powder; the percentages are mass percentages.
[0012] The graphite is expanded graphite; and the adhesive is conductive polyaniline.
[0013] The upper mold of the mold is the cathode flow field of the electrode plate, and the lower mold of the mold is the anode flow field of the electrode plate.
[0014] The molded pore-forming material is molded polyvinyl alcohol.
[0015] The shaped polyvinyl alcohol is prepared by the following method:
[0016] S11, mixing polyvinyl alcohol (PVA) and water in a mass ratio of 1:10 to 1:20, heating to 80° C. to 90° C. to obtain a uniform solution; adding a cross-linking agent to the uniform solution, continuing to stir until uniform, to obtain a mixed solution; the mass of the cross-linking agent is 1% to 3% of the mass of the polyvinyl alcohol;
[0017] S12, cooling the mixed solution to room temperature to obtain a cooled mixed solution; introducing the cooled mixed solution into a plate water surface flow field mold to obtain polyvinyl alcohol having a flow field shape;
[0018] S13, drying the polyvinyl alcohol having the flow field shape at 40° C. to 60° C. to obtain shaped polyvinyl alcohol.
[0019] As a preferred embodiment, in step S11,
[0020] The cross-linking agent is borax.
[0021] The stirring time is 20 to 30 minutes, so that the borax can be evenly dispersed.
[0022] As a preferred embodiment, in step S02,
[0023] The pressurization pressure is 25-35 MPa; the pressurization time is 15-20 minutes. The heating is carried out in an inert gas; the inert gas is preferably argon. By heating, the PVA undergoes high-temperature decomposition, forming a water channel structure inside the plate, and obtaining an integrated bipolar plate with cathode flow channels, anode flow channels and water flow channels.
[0024] As a preferred embodiment, in step S03,
[0025] The time of the vacuum pressure impregnation is preferably 4 to 6 hours; the pressure of the vacuum pressure impregnation is preferably 0.4 to 0.6 MPa. Through impregnation, the holes of the plate can be blocked to ensure the airtightness of the plate.
[0026] The rinsing is performed with clean water for 30 to 60 minutes.
[0027] The curing is performed in hot water at 90 to 95° C. for 30 to 60 minutes.
[0028] On the other hand, an embodiment of the present application further provides an integrated fuel cell bipolar plate, which is prepared by the above-mentioned preparation method.
[0029] Compared with the prior art, the technical solution of the embodiment of the present invention has the following beneficial effects: This application uses polyvinyl alcohol as a pore-forming material, expanded graphite as a graphite material, borax as a cross-linking agent, and conductive polyaniline as an adhesive, and adopts a direct preparation method to prepare an integrated fuel cell bipolar plate. Through the method of the present application, there is no need to integrate by bonding and laminating, which reduces the production process, improves production efficiency, and reduces production costs. The preparation method of the present application is simple and easy to implement, which greatly shortens the preparation cycle of the bipolar plate, has high production efficiency, and can be used for large-scale production of bipolar plates. The prepared integrated fuel cell bipolar plate has low contact resistance, high molding efficiency, good performance, and can meet the use needs of fuel cells. DETAILED DESCRIPTION
[0030] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0031] In addition, the technical solutions between the various embodiments can be combined with each other, but it must be based on the fact that ordinary technicians in the field can implement it. When the combination of technical solutions is contradictory or cannot be implemented, it should be deemed that such combination of technical solutions does not exist and is not within the scope of protection required by the present invention.
[0032] At present, the existing bipolar plates have the problems of long preparation time and low production efficiency. In order to solve the above technical problems, the embodiment of the present application provides a method for preparing an integrated fuel cell bipolar plate, comprising the following steps:
[0033] S01, evenly laying a first mixed powder in a mold to obtain a first mixed powder layer; evenly laying a formed pore-forming material on the first mixed powder layer to obtain a formed pore-forming material layer; evenly laying a second mixed powder on the formed pore-forming material layer to obtain an integrated plate powder;
[0034] S02, press-forming the integrated plate powder at 140° C. to 160° C. to obtain an integrated plate; heating the integrated plate to 200° C. to 230° C. and maintaining for 2 h to 3 h to obtain an integrated bipolar plate having a cathode flow channel, an anode flow channel and a water flow channel;
[0035] S03, immersing the integrated bipolar plate having the cathode flow channel, the anode flow channel and the water flow channel in acrylic glue, rinsing after vacuum pressure immersion, and then curing to obtain an integrated fuel cell bipolar plate.
[0036] The present invention uses polyvinyl alcohol as a pore-forming material, expanded graphite as a graphite material, borax as a cross-linking agent, and conductive polyaniline as an adhesive to prepare an integrated fuel cell bipolar plate by a direct preparation method. The present invention method does not require integration by bonding, which reduces production processes, improves production efficiency, and reduces production costs.
[0037] The amount of pore-forming material used varies according to the plate design. The pore-forming agent will eventually disappear, and the mass depends on the size and structural design of the water surface flow channel, and does not affect the overall forming effect of the plate.
[0038] As a preferred embodiment, in step S01,
[0039] The first mixed powder and the second mixed powder are both graphite / adhesive mixed powders; the mass ratio of the first mixed powder to the second mixed powder is 1:1.
[0040] The graphite / adhesive mixed powder is prepared by the following method: 75% to 85% of graphite and 15% to 25% of adhesive are uniformly mixed by dry powder spraying to obtain the graphite / adhesive mixed powder; the percentages are mass percentages.
[0041] The graphite is expanded graphite; and the adhesive is conductive polyaniline.
[0042] The upper mold of the mold is the cathode flow field of the electrode plate, and the lower mold of the mold is the anode flow field of the electrode plate.
[0043] The molded pore-forming material is molded polyvinyl alcohol.
[0044] The shaped polyvinyl alcohol is prepared by the following method:
[0045] S11, mixing polyvinyl alcohol (PVA) and water in a mass ratio of 1:10 to 1:20, heating to 80° C. to 90° C. to obtain a uniform solution; adding a cross-linking agent to the uniform solution, continuing to stir until uniform, to obtain a mixed solution; the mass of the cross-linking agent is 1% to 3% of the mass of the polyvinyl alcohol;
[0046] S12, cooling the mixed solution to room temperature (to slow down the cross-linking reaction rate and provide sufficient time for molding) to obtain a cooled mixed solution; introducing the cooled mixed solution into a plate water surface flow field mold to obtain polyvinyl alcohol having a flow field shape;
[0047] S13, drying the polyvinyl alcohol having the flow field shape at 40° C. to 60° C. (drying is performed to reduce moisture and increase the stability of the polyvinyl alcohol structure) to obtain shaped polyvinyl alcohol.
[0048] As a preferred embodiment, in step S11,
[0049] The cross-linking agent is borax.
[0050] The stirring time is 20 to 30 minutes, so that the borax can be evenly dispersed.
[0051] As a preferred embodiment, in step S02,
[0052] The pressurization pressure is 25-35 MPa; the pressurization time is 15-20 minutes. The heating is carried out in an inert gas; the inert gas is preferably argon. By heating, the PVA undergoes high-temperature decomposition, forming a water channel structure inside the plate, and obtaining an integrated bipolar plate with cathode flow channels, anode flow channels and water flow channels.
[0053] As a preferred embodiment, in step S03,
[0054] The time of the vacuum pressure impregnation is preferably 4 to 6 hours; the pressure of the vacuum pressure impregnation is preferably 0.4 to 0.6 MPa. Through impregnation, the holes of the plate can be blocked to ensure the airtightness of the plate.
[0055] The rinsing is performed with clean water for 30 to 60 minutes.
[0056] The curing is performed in hot water at 90 to 95° C. for 30 to 60 minutes.
[0057] In the embodiments of the present application, the solution of the present application can be implemented as long as the operating conditions are controlled within the above range.
[0058] Example 1
[0059] A method for preparing an integrated fuel cell bipolar plate comprises the following steps:
[0060] S01, evenly spread 30g of the first mixed powder in the mold to obtain a first mixed powder layer; evenly spread 9g of the formed pore-forming material on the first mixed powder layer to obtain a formed pore-forming material layer; evenly spread 30g of the second mixed powder on the formed pore-forming material layer to obtain an integrated plate powder;
[0061] S02, press-forming the integrated plate powder at 160° C. to obtain an integrated plate; heating the integrated plate to 220° C. and maintaining for 3 hours to obtain an integrated bipolar plate having a cathode flow channel, an anode flow channel and a water flow channel;
[0062] S03, immersing the integrated bipolar plate having the cathode flow channel, the anode flow channel and the water flow channel in acrylic glue, rinsing after vacuum pressure immersion, and then curing to obtain an integrated fuel cell bipolar plate.
[0063] In step S01,
[0064] The first mixed powder and the second mixed powder are both graphite / adhesive mixed powders; the mass ratio of the first mixed powder to the second mixed powder is 1:1.
[0065] The graphite / adhesive mixed powder is prepared by the following method: 80% of graphite and 20% of adhesive are evenly mixed by dry powder spraying to obtain the graphite / adhesive mixed powder; the percentage is the mass percentage.
[0066] The graphite is expanded graphite; and the adhesive is conductive polyaniline.
[0067] The upper mold of the mold is the cathode flow field of the electrode plate, and the lower mold of the mold is the anode flow field of the electrode plate.
[0068] The molded pore-forming material is molded polyvinyl alcohol.
[0069] The shaped polyvinyl alcohol is prepared by the following method:
[0070] S11, mixing polyvinyl alcohol and water in a mass ratio of 1:10, heating to 80° C. to obtain a uniform solution; adding a cross-linking agent to the uniform solution, continuing to stir until uniform, to obtain a mixed solution; the mass of the cross-linking agent is 3% of the mass of the polyvinyl alcohol;
[0071] S12, cooling the mixed solution to room temperature to obtain a cooled mixed solution; introducing the cooled mixed solution into a plate water surface flow field mold to obtain polyvinyl alcohol having a flow field shape;
[0072] S13, drying the polyvinyl alcohol having the flow field shape at 50° C. to obtain shaped polyvinyl alcohol.
[0073] In step S11, the cross-linking agent is borax; and the stirring time is continued for 30 minutes.
[0074] In step S02,
[0075] The pressurization pressure is 30 MPa and the pressurization time is 15 minutes. The heating is performed in an inert gas and the inert gas is argon.
[0076] In step S03,
[0077] The time of the vacuum pressure impregnation is 4 hours; the pressure of the vacuum pressure impregnation is 0.4 MPa.
[0078] The rinsing was performed with clean water for 30 minutes.
[0079] The curing is performed in hot water at 90° C. for 30 minutes.
[0080] The prepared integrated fuel cell bipolar plate was cut and then tested for air tightness and related performance. The results showed that the air tightness of the integrated fuel cell was 0.12sccm and the contact resistance was 4.3mΩ·cm 2 , the conductivity is 354S / cm, that is, the integrated fuel cell bipolar plate obtained in the present application meets the use requirements of the fuel cell and can meet the use needs of the fuel cell.
[0081] Example 2
[0082] A method for preparing an integrated fuel cell bipolar plate comprises the following steps:
[0083] S01, evenly laying a first mixed powder in a mold to obtain a first mixed powder layer; evenly laying a formed pore-forming material on the first mixed powder layer to obtain a formed pore-forming material layer; evenly laying a second mixed powder on the formed pore-forming material layer to obtain an integrated plate powder;
[0084] S02, press-forming the integrated plate powder at 140° C. to obtain an integrated plate; heating the integrated plate to 200° C. and maintaining for 2 hours to obtain an integrated bipolar plate having a cathode flow channel, an anode flow channel and a water flow channel;
[0085] S03, immersing the integrated bipolar plate having the cathode flow channel, the anode flow channel and the water flow channel in acrylic glue, rinsing after vacuum pressure immersion, and then curing to obtain an integrated fuel cell bipolar plate.
[0086] In step S01,
[0087] The first mixed powder and the second mixed powder are both graphite / adhesive mixed powders; the mass ratio of the first mixed powder to the second mixed powder is 1:1.
[0088] The graphite / adhesive mixed powder is prepared by the following method: 75% of graphite and 25% of adhesive are evenly mixed by dry powder spraying to obtain the graphite / adhesive mixed powder; the percentage is the mass percentage.
[0089] The graphite is expanded graphite; and the adhesive is conductive polyaniline.
[0090] The upper mold of the mold is the cathode flow field of the electrode plate, and the lower mold of the mold is the anode flow field of the electrode plate.
[0091] The molded pore-forming material is molded polyvinyl alcohol.
[0092] The shaped polyvinyl alcohol is prepared by the following method:
[0093] S11, mixing polyvinyl alcohol and water in a mass ratio of 1:20, and heating to 90° C. to obtain a uniform solution; adding a cross-linking agent to the uniform solution, and continuing to stir until uniform, to obtain a mixed solution; the mass of the cross-linking agent is 1% of the mass of the polyvinyl alcohol;
[0094] S12, cooling the mixed solution to room temperature to obtain a cooled mixed solution; introducing the cooled mixed solution into a plate water surface flow field mold to obtain polyvinyl alcohol having a flow field shape;
[0095] S13, drying the polyvinyl alcohol having the flow field shape at 40° C. to obtain shaped polyvinyl alcohol.
[0096] In step S11, the cross-linking agent is borax, and the stirring time is continued for 20 minutes, so that the borax can be evenly dispersed.
[0097] In step S02,
[0098] The pressurization pressure is 25 MPa and the pressurization time is 20 minutes. The heating is performed in an inert gas and the inert gas is argon.
[0099] In step S03,
[0100] The time of the vacuum pressure impregnation is 5 hours; the pressure of the vacuum pressure impregnation is 0.5 MPa.
[0101] The rinsing was performed with clean water for 45 minutes.
[0102] The curing is performed in hot water at 95° C. for 45 minutes.
[0103] The prepared integrated fuel cell bipolar plate was cut and then tested for air tightness and related performance. The results showed that the air tightness of the integrated fuel cell was 0.13sccm and the contact resistance was 4.2mΩ·cm 2 , the conductivity is 353S / cm, that is, the integrated fuel cell bipolar plate obtained in the present application meets the use requirements of the fuel cell and can meet the use needs of the fuel cell.
[0104] Example 3
[0105] A method for preparing an integrated fuel cell bipolar plate comprises the following steps:
[0106] S01, evenly laying a first mixed powder in a mold to obtain a first mixed powder layer; evenly laying a formed pore-forming material on the first mixed powder layer to obtain a formed pore-forming material layer; evenly laying a second mixed powder on the formed pore-forming material layer to obtain an integrated plate powder;
[0107] S02, press-forming the integrated plate powder at 150° C. to obtain an integrated plate; heating the integrated plate to 230° C. and maintaining for 3 hours to obtain an integrated bipolar plate having a cathode flow channel, an anode flow channel and a water flow channel;
[0108] S03, immersing the integrated bipolar plate having the cathode flow channel, the anode flow channel and the water flow channel in acrylic glue, rinsing after vacuum pressure immersion, and then curing to obtain an integrated fuel cell bipolar plate.
[0109] In step S01,
[0110] The first mixed powder and the second mixed powder are both graphite / adhesive mixed powders; the mass ratio of the first mixed powder to the second mixed powder is 1:1.
[0111] The graphite / adhesive mixed powder is prepared by the following method: 85% of graphite and 15% of adhesive are evenly mixed by dry powder spraying to obtain the graphite / adhesive mixed powder; the percentage is the mass percentage.
[0112] The graphite is expanded graphite; and the adhesive is conductive polyaniline.
[0113] The upper mold of the mold is the cathode flow field of the electrode plate, and the lower mold of the mold is the anode flow field of the electrode plate.
[0114] The molded pore-forming material is molded polyvinyl alcohol.
[0115] The shaped polyvinyl alcohol is prepared by the following method:
[0116] S11, mixing polyvinyl alcohol and water in a mass ratio of 1:15, heating to 85° C. to obtain a uniform solution; adding a cross-linking agent to the uniform solution, continuing to stir until uniform, to obtain a mixed solution; the mass of the cross-linking agent is 2% of the mass of the polyvinyl alcohol;
[0117] S12, cooling the mixed solution to room temperature to obtain a cooled mixed solution; introducing the cooled mixed solution into a plate water surface flow field mold to obtain polyvinyl alcohol having a flow field shape;
[0118] S13, drying the polyvinyl alcohol having the flow field shape at 50° C. to obtain shaped polyvinyl alcohol.
[0119] In step S11, the cross-linking agent is borax, and the stirring time is continued for 30 minutes, so that the borax can be evenly dispersed.
[0120] In step S02,
[0121] The pressurization pressure is 28 MPa and the pressurization time is 18 minutes. The heating is performed in an inert gas, which is argon.
[0122] In step S03,
[0123] The time of the vacuum pressure impregnation is 5 hours; the pressure of the vacuum pressure impregnation is 0.6 MPa.
[0124] The rinsing was performed with clean water for 60 minutes.
[0125] The curing is performed in hot water at 92° C. for 60 minutes.
[0126] The prepared integrated fuel cell bipolar plate was cut and then tested for air tightness and related performance. The results showed that the air tightness of the integrated fuel cell was 0.14 sccm and the contact resistance was 4.3 mΩ·cm. 2, the conductivity is 356S / cm, that is, the integrated fuel cell bipolar plate obtained in the present application meets the use requirements of the fuel cell and can meet the use needs of the fuel cell.
[0127] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing an integrated fuel cell bipolar plate, characterized in that: The steps include: S01, evenly laying a first mixed powder in a mold to obtain a first mixed powder layer; evenly laying a formed pore-forming material on the first mixed powder layer to obtain a formed pore-forming material layer; evenly laying a second mixed powder on the formed pore-forming material layer to obtain an integrated plate powder; S02, press-forming the integrated plate powder at 140° C. to 160° C. to obtain an integrated plate; heating the integrated plate to 200° C. to 230° C. and maintaining for 2 h to 3 h to obtain an integrated bipolar plate having a cathode flow channel, an anode flow channel and a water flow channel; S03, immersing the integrated bipolar plate having the cathode flow channel, the anode flow channel and the water flow channel in acrylic glue, rinsing after vacuum pressure immersion, and then curing to obtain an integrated fuel cell bipolar plate.
2. The method for preparing an integrated fuel cell bipolar plate according to claim 1, characterized in that: In step S01, the first mixed powder and the second mixed powder are both graphite / adhesive mixed powder; and the mass ratio of the first mixed powder to the second mixed powder is 1:
1.
3. The method for preparing an integrated fuel cell bipolar plate according to claim 2, characterized in that: The graphite / adhesive mixed powder is prepared by the following method: 75% to 85% of graphite and 15% to 25% of adhesive are evenly mixed by dry powder spraying to obtain the graphite / adhesive mixed powder; the percentage is mass percentage; the graphite is expanded graphite; and the adhesive is conductive polyaniline.
4. The method for preparing an integrated fuel cell bipolar plate according to claim 1, characterized in that: In step S01, the upper mold of the mold is the cathode flow field of the electrode plate, and the lower mold of the mold is the anode flow field of the electrode plate; the molded pore-forming material is molded polyvinyl alcohol.
5. The method for preparing an integrated fuel cell bipolar plate according to claim 4, characterized in that: The shaped polyvinyl alcohol is prepared by the following method: S11, mixing polyvinyl alcohol and water in a mass ratio of 1:10 to 1:20, heating to 80° C. to 90° C. to obtain a uniform solution; adding a crosslinking agent to the uniform solution, continuing to stir until uniform, to obtain a mixed solution; the mass of the crosslinking agent is 1% to 3% of the mass of the polyvinyl alcohol; S12, cooling the mixed solution to room temperature to obtain a cooled mixed solution; Introducing the cooled mixed solution into a plate water surface flow field mold to obtain polyvinyl alcohol having a flow field shape; S13, drying the polyvinyl alcohol having the flow field shape at 40° C. to 60° C. to obtain shaped polyvinyl alcohol.
6. The method for preparing an integrated fuel cell bipolar plate according to claim 5, characterized in that: In step S01, in step S11, The cross-linking agent is borax; and the stirring time is 20 to 30 minutes.
7. The method for preparing an integrated fuel cell bipolar plate according to claim 1, characterized in that: In step S02, the pressurization pressure is 25 to 35 MPa; the pressurization time is 15 to 20 minutes; and the heating is performed in an inert gas.
8. The method for preparing an integrated fuel cell bipolar plate according to claim 1, characterized in that: In step S03, the time of the vacuum pressure impregnation is preferably 4 to 6 hours; the pressure of the vacuum pressure impregnation is preferably 0.4 to 0.6 MPa.
9. The method for preparing an integrated fuel cell bipolar plate according to claim 1, characterized in that: In step S03, the rinsing is performed with clean water for 30 to 60 minutes; The curing is performed in hot water at 90 to 95° C. for 30 to 60 minutes.
10. An integrated fuel cell bipolar plate, characterized in that: The integrated fuel cell bipolar plate is prepared by the preparation method described in any one of claims 1 to 9.
Citation Information
Patent Citations
Method for preparing direct methanol fuel cell composite bipolar plate
CN101635358A
Preparation method and application of bipolar plate
CN109921053A
Method for preparing graphite bipolar plate through one-step forming
CN113437320A
Flexible graphite bipolar plate as well as preparation method and application thereof
CN114566669A
Fuel cell graphite composite bipolar plate and preparation method thereof
CN117901434A